Expert Consensus on Tiered Detection of Newly Emerging and Outbreak Respiratory Infectious Pathogens (2024) - Chinese Hospital Association Clinical Microbiology Laboratory Specialized Committee (Xiehe Yixue Zazhi)
In recent years, respiratory infectious disease outbreaks have been continually emerging internationally, posing significant challenges to global public health and healthcare systems. How to promptly implement a tiered screening and detection strategy that systematically covers common clinical infectious pathogens causing acute respiratory infections, pathogens causing chronic respiratory infections, and rare respiratory infectious pathogens, while focusing on potential newly emerging respiratory infectious pathogens, and quickly identifying the causative microorganisms, has become a critical issue in clinical diagnosis. To address this issue, the Chinese Hospital Association Clinical Microbiology Laboratory Specialized Committee assembled a multidisciplinary group of experts to summarize the practical experience accumulated in domestic laboratory testing.Incombination with the latest international research progress, they developed the Expert Consensus on Tiered Detection of Newly Emerging and Outbreak Respiratory Infectious Pathogens (2024). This consensus analyzes the major characteristics of newly emerging and outbreak respiratory infections, considers patient population characteristics, and proposes a three-tiered detection strategy that includes traditional microbiological morphology, culture, immunology, molecular biology, and metagenomic sequencing methods. It defines the target pathogens and recommends detection methods at different stages, providing guidance and reference for improving the diagnostic capacity for newly emerging and outbreak respiratory infectious diseases.